2015
DOI: 10.4238/2015.may.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Association between the rs189037 single nucleotide polymorphism in the ATM gene promoter and cognitive impairment

Abstract: ABSTRACT. The aim of this study was to explore the existence of a relationship between the rs189037 single nucleotide polymorphism (SNP) of the ataxia telangiectasia mutated (ATM) gene and cognitive impairment in the elderly (aged 60 years and above). In a cohort, 505 residents of Suinung City were consecutively recruited and their cognitive function was measured using a 30-point Mini-Mental State Examination (MMSE). The subjects were divided into cognitive impairment group and control group on the basis of MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…ATM gene has been shown to play an important role in DNA repair. Previous studies have reported correlations between DNA repair capacity and the regulation of ATM expression [ 33 , 34 ]. It has been demonstrated that the aberrant overexpression of miR-421 may down-regulated ATM , therefore, can lead to SKX squamous cell carcinoma [ 35 ].In addition, it has been shown that miR-203 may be responsible for ATM down-regulation in breast cancers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATM gene has been shown to play an important role in DNA repair. Previous studies have reported correlations between DNA repair capacity and the regulation of ATM expression [ 33 , 34 ]. It has been demonstrated that the aberrant overexpression of miR-421 may down-regulated ATM , therefore, can lead to SKX squamous cell carcinoma [ 35 ].In addition, it has been shown that miR-203 may be responsible for ATM down-regulation in breast cancers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs189037 of ATM gene was genotyped by using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) as previously described. [ 34 ] Forward primer was 5′-GCTGCTTGGCGTTGCTT-3′ and reverse primer was 5′-CATGCGATTGGCGGTCTGG-3′ (TaKaRa, Dalian, China). The PCR reaction was performed in 25 μL total volume containing 2 μL of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…SNP rs189037 of the ATM gene was genotyped using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). Forward primer 5′-GCTGCTTGGCGTTGCTT-3′ and reverse primer 5′-CATGCGATTGGCGGTCTGG-3′ (TaKaRa, Dalian, China) were designed and synthesized as described in our previous study [ 28 ]. The amplification conditions were used as follows: initial denaturation at 94 °C for 3 min, followed by 30 cycles of amplification which included denaturation at 94 °C for 30 s, annealing at 55 °C for 30 s, and extension at 72 °C for 30 s with a final extension of 5 min at 72 °C.…”
Section: Methodsmentioning
confidence: 99%